Abu Zubaydah v. Lithuania (Eur. Ct. H.R.). (6th November 2018) - Cerna, Christina M.
Abstract : Following the events of September 11, 2001, the CIA established "the High-Value Detainee Program, " also known as the Rendition Detention Interrogation Program. On December 14, 2014, the U.S. Senate Select Committee on Intelligence released a heavily redacted 500-page Executive Summary of the Committee's "Study of the Central Intelligence Agency's Detention and Interrogation Program." The full Committee Study is more than 6, 700 pages long and remains classified. The release of the Executive Summary, however, disclosed new facts and provided a significant amount of new information to the European Court of Human Rights—mostly based on CIA classified documents—about the CIA extraordinary rendition and secret detention operations; their foreign partners or cooperators; as well as the plight of certain detainees, including Abu-Zubaydah. Abu Zubaydah v. Lithuania is the European Court's first judgment to have taken advantage of the information provided in the Senate Committee's Executive Summary of its Study.